Preschool teachers’ awareness, content knowledge, pedagogical skills and children’s emergent literacy in Ibadan, Oyo State (2018)
The primary function of language is communication. Learning about literacy begins long before children can read and write in the conventional sense. Most children at risk of school failure benefit more from high quality experiences as effective instruction in the early years can have a great impact on children's language and literacy development. In the absence of such effective instruction, differences in children understanding and use of language may vary greatly by age three. Reading skills provide a solid foundation for children's academic success. Children who read well tend to read more and, as a result, acquire more knowledge in many content domains. Although, many children learn to read without significant problem, but so many are having serious difficulty in reading which stems from lack of basic skills in emergent literacy. This study adopted a survey design of the correlational type. Random sampling technique was used to select three local government areas in Ibadan metropolis. Purposive sampling technique was used to select 10 participating preschools from each local government area with thirty (30) preschool teachers and (302) preschool children in all. Two validated instruments were adapted namely Preschool Teachers' Awareness, Knowledge of and Pedagogical Skills in Emergent Literacy Questionnaire (Pre-TAKE) and Preschool Children's Emergent literacy Assessment (PCELA) with reliability coefficient at (a = .89) and (r = .51) respectively. The data collected were analysed using multiple regression analysis to test the hypotheses. The findings revealed a significant relationship between teachers' awareness (r = 0.047; p < 0.05), content knowledge (r = 0.000; p<0.05) and the level of children's emergent literacy respectively, but there was no significant relationship between teachers' pedagogical skills (r = 0.91 ;p>0. 05) and the level of children's emergent literacy in Ibadan metropolis. In view of these findings, it was recommended that preschool teachers should be aware of children's emergent literacy and equipped with an extensive content knowledge, a repertoire of effective teaching strategies and decision making and problem solving skills to cater for children's needs. Through proper training and support, preschool teachers can acquire the expertise in literacy instruction and thus be successful in promoting literacy skills and motivation of preschool children.